Adapting to the Digital Era : Transformations in the audit profession and the emergence of new skills. - LAHSINI , Hind; TAOUAB , Omar (Revue Internationale des Sciences de Gestion, 2024)
Digital transformation is fundamentally reshaping the professional landscape of auditing, with the emergence of technologies such as artificial intelligence, data analytics, and blockchain. This study explores the impact of this digital revolution on the auditing profession, shedding light on the new skills required for auditors and the adaptations made by audit firms. Through an in-depth literature review and interviews with experienced auditors, we examine how digital transition enhances efficiency while influencing the nature of audit work. Our findings indicate that, although technology transforms audit processes, it also reinforces the essential role of auditors by preserving subjectivity and professional judgment. Practical implications of this study include recommendations for auditors to continuously adapt to digital changes and the importance of educational institutions adjusting training programs. This research contributes to understanding the evolution of the auditing profession in the digital era, emphasizing the significance of ongoing adjustment and the acquisition of diverse skills.